Analisis Foto Tari Remo Di Media Sosial Instagram @surabaya Melalui Metode EDFAT (entire, detail, frame, angle, time) - Sarjono, Doni; Fadeli, Muhammad; Ekantoro, Julyanto (Brand Communication, 2024)
With the advent of digital technology, the dissemination of information has accelerated, particularly through various types of photo media such as brochures, magazines, and newspapers. In the media industry, photojournalism, which uses visual images to quickly convey events, is highly significant. Photography is an effective tool for communication and documentation. With pioneers like Alex Mendur, photojournalism has a long history in Indonesia and around the world. The EDFAT method (Entire, Detail, Frame, Angle, and Time) was introduced by the Walter Cronkite School of Journalism and Telecommunication at Arizona State University. To obtain complete and informative images, EDFAT helps photographers optimize essential shooting elements. Using the EDFAT method, this research aims to analyze photos of the Remo dance posted on the Instagram account @surabaya. The research method employed is descriptive qualitative. The analysis results show that the images have consistency in aspects such as the entire scene, details, framing, angles, and timing. While various perspectives such as eye level, high shot, and long shot are used to provide visual variety, the frame analysis shows good photo composition with an emphasis on the dancer as the main subject. These photos were taken during the day with the best natural lighting. Thus, the EDFAT method greatly aids photographers in creating comprehensive and engaging journalistic photos.